2011
DOI: 10.1111/j.1524-4725.2011.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Periungual Warts with Diluted Bleomycin Using Translesional Multipuncture Technique: A Pilot Prospective Study

Abstract: Translesional multipuncture treatment with a low concentration (0.1 U/mL) of bleomycin is an effective modality for periungual warts that results in minimal side effects. Larger controlled studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 24 publications
1
30
0
2
Order By: Relevance
“…Alghamdi and Khurram in their two reported studies utilized the multipuncture techniques to administer very low concentrations (0.1 U/mL) of bleomycin translesionally for periungual and plantar warts. Their clearance rates were 86.6% and 74%, respectively …”
Section: Discussionmentioning
confidence: 97%
“…Alghamdi and Khurram in their two reported studies utilized the multipuncture techniques to administer very low concentrations (0.1 U/mL) of bleomycin translesionally for periungual and plantar warts. Their clearance rates were 86.6% and 74%, respectively …”
Section: Discussionmentioning
confidence: 97%
“…The strength of bleomycin used has usually been 1 U mL À1 , equivalent to 1 mg mL À1 , but weaker strengths of 0Á5 mg mL À1 or even 0Á1 mg mL À1 seem to produce similar effects. 100,101 The introduction of bleomycin into the skin is painful, and local anaesthesia, either before or together with administration of bleomycin, helps to make the procedure more comfortable. The effect of bleomycin on the wart produces some pain that lasts a day or two, and then necrosis develops with a black eschar that separates after a few days.…”
mentioning
confidence: 99%
“…This obvious response to treatment makes it difficult to conduct double-blinded trials, and many studies have been open studies or have used bleomycin in comparison with saline injection or cryotherapy. Open studies have suggested clearance rates of approximately 20-90% of treated warts with one or more treatments, 101,102 with most reporting a patient response rate of approximately 65-85%. 101,103 Several trials of intralesional bleomycin have used saline as a placebo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…to the literature addressing the treatment of one of the most common conditions in our practices: verrucae vulgaris. 1 Bleomycin has been employed for decades among a number of therapeutic options for warts, but concerns persist about discomfort, systemic absorption, Raynaud's phenomenon, and long-term tissue destruction or scarring.…”
mentioning
confidence: 99%